The role of FAM111B in the malignant progression and molecular regulation of human glioma through the PI3K/Akt pathway - Heng Wang; Junrou Zhu; Haiyang Wang; Wenhao Zheng; Linjie Wang; Jinhao Zhu; Zheng Wang; Quan Du (Chinese Neurosurgical Journal)
Abstract Background Gliomas represent the most prevalent primary neoplasm in the adult central nervous system. Despite advancements in therapeutic modalities, such as surgical intervention, radiotherapy, chemotherapy, and tumor treatment, the 5-year survival rate of glioma patients remains low. Therefore, there is an urgent need to develop additional treatment methods. Recent studies have suggested that FAM111B is involved in DNA repair, cell cycle regulation, and apoptosis. FAM111B mutations and overexpression are related to cancer. Methods We found that FAM111B was significantly overexpressed in glioma tissues compared to the adjacent tissues by analyzing data from the TCGA_GBM&LGG and CGGA databases. Moreover, overexpression of FAM111B was associated with shorter overall survival, and disease-specific survival and tended to increase with disease stage progression. Cellular experiments confirmed these results. These results suggest that overexpression of FAM111B promotes the proliferation, migration, and invasion of glioma cells, whereas the knockdown of FAM111B inhibits these activities. We also found that FAM111B regulated glioma cell proliferation, migration, and invasion via the PI3K/AKT pathway. Results FAM111B is capable of enhancing the proliferation, invasion, and migration capabilities of glioma cells and promotes the malignant progression of glioma via the PI3K/Akt signaling pathway. Conclusions This is the first study to demonstrate that FAM111B plays a crucial role in the proliferation, migration, and invasion of glioma cells. The malignant phenotype of FAM111B has also been shown to be closely associated with the PI3K/AKT pathway. FAM111B may be a predictive biomarker and a potential therapeutic target for gliomas.